Dual-palindrome-incorporated hand-in-hand self-linking bidirectional DNA amplifier within exogenous near-infrared light stimulation for high-performance imaging in living biosystems - Zhang, Tian-Tian; Sun, Xiao-Ming; Chen, Wei-Lin; Chen, Xiao-Xue; Li, Cheng-Yu (Talanta (Oxford), 2025)
Although the potency of DNA amplifiers-constructed biosensors for imaging disease biomarkers in living biosystems, they continue to face two challenges: (i) intricate multi-pathway amplification cascades in biosensing designs and (ii) suboptimal detection precision due to uncontrollable pre-activation during bio-delivery. In this contribution, we have brought the following viable resolutions. First, a catalytic hairpin assembly (CHA) routine is incorporated with a dual-palindrome that works like two pairs of hands to self-link CHA-amplified intermediate nucleic acids units, enabling a streamlined two-round signal intensification to enhance sensitivity. Thereafter, one DNA component is conducted with the insertion of a photocleavage-coupler, by which the biosensor can be precisely stimulated via exogenous 808 nm near-infrared (NIR) light-converted upconversion luminescence to recognize the analysis subjects in a controllable action. With the aim of conceptual presentation, this dual-palindrome-incorporated hand-in-hand self-linking bidirectional DNA amplifier stimulated by exogenous NIR light exhibits ultra-sensitive solution detection of various cancers-associated microRNA-155. More deeply, the biosensing toolbox can serve for high-performance imaging of low-abundance biomarkers at the real-word context of living cells and in vivo, boosting the advancement of DNA amplifiers in medical diagnostics. Dual-palindrome is incorporated to construct a hand-in-hand self-linking bidirectional DNA amplifier. Within exogenous near-infrared light stimulation, this biosensor is employed to conduct high-performance microRNA imaging in living biosystems. [Display omitted] •A hand-in-hand self-linking bidirectional DNA amplifier is constructed.•Exogenous near-infrared light is used to stimulate the DNA amplifier.•The biosensor exhibits ultra-sensitive detection competence for microRNA-155.•High-performance imaging in living cells and in vivo is presented.